Nowhere in the Middle Ages. - Lochrie, Karma (Middle Ages series., 2016)
"Literary and cultural historians typically cite Thomas More's 1516 Utopia as the source of both a genre and a concept. Karma Lochrie rejects this origin myth of utopianism along with the assumption that people in the Middle Ages were incapable of such thinking. In Nowhere in the Middle Ages, Lochrie reframes the terms of the discussion by revealing how utopian thought was, in fact, "somewhere" in the Middle Ages. In the process, she transforms conventional readings of More's Utopia and challenges the very practice of literary history today"--Publisher's description